2021
DOI: 10.1111/1751-7915.13836
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma harzianum cerato‐platanin enhances hydrolysis of lignocellulosic materials

Abstract: Considering its worldwide abundance, cellulose can be a suitable candidate to replace the fossil oilbased materials, even if its potential is still untapped, due to some scientific and technical gaps. This work offers new possibilities demonstrating for the first time the ability of a cerato-platanin, a small fungal protein, to valorize lignocellulosic Agri-food Wastes. Indeed, cerato-platanins can loosen cellulose rendering it more accessible to hydrolytic attack. The cerato-platanin ThCP from a marine strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Studies demonstrated that CPs could bind to and weaken lignocellulosic materials, acting similarly to plant expansins and facilitating access to cellulolytic enzymes [50,51]. This characteristic has been reported in the CP of Ceratocystis populicola [51], Moniliophthora perniciosa [52], Fusarium graminearum [53], and Trichoderma harzianum [54]. In T. reesei, CPs were found in the secretome during fermentation processes in sugarcane bagasse [55].…”
Section: Discussionmentioning
confidence: 81%
“…Studies demonstrated that CPs could bind to and weaken lignocellulosic materials, acting similarly to plant expansins and facilitating access to cellulolytic enzymes [50,51]. This characteristic has been reported in the CP of Ceratocystis populicola [51], Moniliophthora perniciosa [52], Fusarium graminearum [53], and Trichoderma harzianum [54]. In T. reesei, CPs were found in the secretome during fermentation processes in sugarcane bagasse [55].…”
Section: Discussionmentioning
confidence: 81%
“…These data are of particular interest to optimize the pretreatment conditions, whose impact on enzymatic hydrolysis is not merely related to the degree of delignification [4]. In some cases, positive impact of pretreatment method is due to the superficial alteration that some solvent/catalysts (e.g., surfactants) can provide to the lignin fraction of the biomass [5,6].…”
mentioning
confidence: 99%